The Implementation of Dialogical Leadership in the Management of Educational Institutions at Pesantren Bina Insan Mulia - Ade Aspandi; Iman Subasman; Aip Syarifudin; Muhammad Azhar Muttaqin; Nur Luthfiyani Fajrin Mima; Agus Ramanto (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to analyze the implementation of dialogical leadership in the management of educational institutions at Pesantren Bina Insan Mulia, Cirebon, through the lens of Paulo Freire’s theoretical perspective. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis. Thematic analysis was applied to identify patterns and meanings from participants’ experiences. The findings reveal two major insights: first, dialogical leadership fosters managerial and curricular transformation that integrates pesantren traditions with modern competencies; second, it strengthens the pesantren’s role in developing students’ competencies according to their talents and aspirations while enhancing its contributions to the surrounding community. This research highlights that dialogical leadership plays a pivotal role in shaping a humanistic, participatory, and transformative educational model, demonstrating that pesantren can guide students authentically toward achieving their aspirations in line with their individual potentials.